THU0011 MIR-223 expression in serum and CD3+ peripheral cells of rheumatoid arthritis. (23rd January 2014) - Muscari, I.; Giannitti, C.; Niccolini, S.; Fineschi, I.; Sebastiani, G.D.; Prevete, I.; Iuliano, A.; Balistreri, E.; Gennai, I.; Minisola, G.; Spreafico, A.; Galeazzi, M.
Abstract : Background: We have recently demonstrated that miR-223 is up-regulated in peripheral blood and synovial CD3+T lymphocytes (TL) from Rheumatoid Arthritis (RA) patients compared to healthy controls (1, 2) suggesting that miR-223 could contribute to the pathogenesis. Evidence exists that miRNAs may circulate in a highly stable form in plasma and serum (3). Objectives: To evaluate miR-223 levels in peripheral CD3+TL of RA patients, at baseline (BL) and after 6 months of biological therapies; to evaluate miR-223 levels in sera from RA patients in comparison to healthy donors. Methods: miR-223 expression in peripheral blood CD3+TL was analyzed in 8 RA patients treated with anti-TNFα agents (3: Etanercept; 2: Adalimumab; 1: Infliximab; 2: Golimumab) and 10 treated with IL6-R antagonist (Tocilizumab) at standard dosage for 6 months. Circulating CD3+TL were isolated with Lympholythe-H (Cederline) and Pan T Cell Isolation Kit (Milteny). Total RNA was extracted with TRIzol (Invitrogen). qPCR was performed following miScript PCR System (TaqMan microrna assay, Applied Biosystem). Wilcoxon test was used to perform statistical analysis. Serum samples were obtained from 11 RA patients and 7 healthy donors. Total serum RNA was purified with QIAamp Circulating Nucleic Acid Kit (Qiagen) using a supplementary protocol for biological fluids miRNA isolation. miR-223 expression was analyzed by qPCR following miScript PCR System (Qiagen). Kruskall-Wallis test was used for statistical analysis. The expression level of miR-223 from sera and TL was calculated with Vandesompele Method and miR-223 values was reported as fold change. Informed consent was obtained from all patients. Results: The expression of miR-223 decreased significantly in RA patients after 6-month-therapy with anti-TNFα agents (mean 214.05±182.8 at BL vs. 86.94±52.9 after 6 months; p=0.05). In these patients, mean DAS28 was 6.12 at BL and 4.14 after 6 months (p=0.03). On the contrary, miR-223 levels varied from 394.86±445.5 at BL to 683.22±1258.1 in patients treated with IL6-R antagonist (p=0.55), while mean DAS28 was 5.097 at BL and 3.012 after 6 months (p=0.0039). A significant increase of miR-223 was found in serum compared to controls (7.69±5.1 vs. 1.05±0.8; p<0.05). In the same patients miR-223 also increased in TL (1.07±1.52 vs 0.58±0.22). Conclusions: Weconfirm our previous results that showed an increased level of miR-223 in peripheral CD3+TL from active RA. An increased level of serum miR-223 was also demonstrated, for the first time. In addition, we found that anti-TNFα agents may reduce miR-223 levels, while, in tocilizumab-treated patients miR-223 remained essentially unchanged. This finding suggests thatmiR-223 level may be affected by the different mechanism of action of the used therapy and not by the disease activity status. Further studies are required to confirm our preliminary data, to clarify the role of miR-223 in RA and to validate miR-223 as a potential useful biomarker of disease Ackowledhements: This study is supported by FIRA onlus 2009 (Fondazione Italiana per la Ricerca sull'Artrite) and Regione Toscana Progetto POR CReO FESR 2007-2013. References: Fulci V et al. Hum Immunol 2010;71:206-11. Sebastiani GD et al. Clin Exp Rheumatol 2011;29:1058-1059. Kroh EM et al. Methods 2010;50298–301. Disclosure of Interest: None Declared